THE B+TREES BASED ON THE SYSTEM OF RESIDUAL CLASSES AND ITS USE IN LARGE KNOWLEDGE BASES - A. V. Malikov; V. S. Voronkin; D. M. Aghajanyan; P. P. Taraskevich (Современная наука и инновации)
This paper explores the usage of an index that supports hierarchy between data as well as parallel processing in the field of knowledge systems and intelligent systems. Also, the paper analyses the position of such an index in an intelligent system, tries to identify flaws typical to databases used in intelligent systems, examines the structure of an index and the process of encoding keys in it